Emotional writing dan focus group therapy: upaya penanganan body dissatisfaction pada remaja - Pentarina Intan Laksmitawati; Rudianto Jati Widigdo; Dwiky Nuari (Seminar Nasional Bimbingan dan Konseling Jambore Konseling 3)
Teenagers have many changes, like psychologically and psychally. Based on the above exposure researchers see the importance of holding the program Emotional Writing and Focus Group Therapy which is a program development guidance based group therapy. Adolescence is a time of arrival of puberty which is the transition from childhood to adulthood. At this time the individual trying to find his identity with emotional writing. The target of the program is the early semester student experiencing body dissatisfaction, to find out the exact target, the researchers use a scale of body dissatisfaction. The goal of the program is as a strategy of increased confidence and self-esteem in teens. The methods used in the implementation of this program include planing stage, the stage of implementation, and evaluation. The result of the execution of a program are expressed in percentage form, and the program was included in the rankings either.